Should the central bank issue e-money? - Charles M. Kahn; Francisco Rivadeneyra; Tsz-Nga Wong (Bank of Canada, 2018)
Should a central bank take over the provision of e-money, a circulable electronic liability? We discuss how e-money technology changes the tradeoff between public and private provision, and the tradeoff between e-money and a central bank's existing liabilities like bank notes and reserves. The tradeoffs depend on i) the technological setup of the e-money system (as a token or an account; centralized or decentralized); ii) the potential improvement in the implementation and transmission of monetary policy; iii) the risks to safety and privacy from cyber attacks; and iv) the uncertain impact on banks' efficiency and financial stability. The most compelling argument for central banks to issue e-money is to address competition problems in the banking sector.
Keywords: E42; E51; E58; 330; Digital currencies; Payment clearing and settlement systems; Financial services; Bank notes